The rise of china : implications for india - Pant, Harsh V. ([S.l.] : Cambridge University Press India Pvt. Ltd., 2012)
The rise of China as an emerging power and as the most likely challenger to the global preponderance of the US is already having a significant impact across the globe. This phenomenon is being debated and analysed at various levels. In India too, it is generating a lot of excitement. On the one hand, it is considered to be an opportunity and on the other, a challenge. This book is an attempt at exploring the multi-dimensional nature of the rise of China and its implications for India. The contributors in this volume have examined various aspects of China's rise such as domestic developments, foreign policy agenda, and its position on issues related to India from an Indian perspective. The book will appeal to undergraduate and graduate students of International Relations across the world. Foreign policy experts, and anyone interested in China-India relations should also find the book to be of interest.
Keywords: China; India; International relations; Political science